Odpowiedzi

Najlepsza Odpowiedź!
2009-11-18T14:17:50+01:00
³√3 i 3/8 -(-3²)² ÷ 1 i 1/2
-------------------------------------- =
√2 i 1/4 -(-1 i 2/3)² × 2 i 4/10

³√27/8 - 9² ÷3/2
----------------------------- =
√9/4 - (-5/3)² × 24/10

3/2 - 81 ÷ 3/2
---------------------- =
3/2 - 25/9 × 24/10

3/2 - 81 × 2/3
-------------------- =
3/2 - 5/9 × 24/2

3/2 - 54
-----------------=
3/2 - 5/9 ×12

3/2 - 54
---------------=
3/2 - 60/9

3/2 - 54
--------------=
3/2 - 20/3

3/2 - 108/2
------------------=
9/6 - 40/6

-105/2
----------=
-31/6

-105/2 × (-6/31) =

-105 × (-3/31)=

315/31= 10 i 5/31